Incidental Pulmonary Nodules Reported on CT Abdominal Imaging: Frequency and Factors Affecting Inclusion in the Hospital Discharge Summary. Issue 6 (1st June 2017) - Bates, Ruth; Plooster, Corbin; Croghan, Ivana; Schroeder, Darrell; McCoy, Christopher
Abstract : Incidental imaging findings require an assessment of risk and clinical relevance, as well as consideration of further evaluation. Incidental findings are common on imaging obtained in the hospital, with pulmonary nodules being among the most frequent findings that may require additional evaluation. We conducted a retrospective study to determine the factors associated with documentation of incidental findings in the hospital discharge summary, using pulmonary nodules reported on abdominal computed tomography (CT) as an example of incidental findings with well‐defined follow‐up guidelines. Between January 1, 2012 and December 31, 2014, 7173 patients underwent in‐patient abdominal CT without concurrent chest CT; of these patients, 62.2% were ≥60 years old, 50.6% were men, and 45.5% were current or former smokers. Incidental pulmonary nodules were reported in 402 patients (5.6%; 95% confidence interval [CI], 5.1%‐6.2%). Based on nodule size, reported size stability, and patients' smoking status, 208 patients (2.9%; 95% CI, 2.5%‐3.3%) required follow‐up surveillance, per the 2005 Fleischner Society guidelines. Of these 208 patients, 48 (23%) received discharge summaries that included documentation of the incidental findings, with 34 summaries including a recommendation for nodule follow‐up and 19 summaries including a time frame for repeat CT. Three factors were positively associated with the inclusion of the pulmonary nodule in the discharge summary: mention of the pulmonary nodule in the summary headings of the radiology report ( P ≤ 0.001), radiologist recommendations for further surveillance ( P ≤ 0.001), and medical discharging service ( P = 0.016). These findings highlight the need for a multidisciplinary systems‐based approach to incidental pulmonary nodule documentation and surveillance.